The impact of job satisfaction facets towards employee work performance in Swiss Inn Hotel, Sungai Petani, Kedah / Norshazlin Pisaal and Nur Atiqah Bohari - Pisaal, Norshazlin; Bohari, Nur Atiqah (2010)
The objective of this study is to identify whether payment, work or advancement opportunities is one of the facets that makes employees improve their work performance and to identify which job satisfaction facets that mostly influenced employees work performance. The population of this study is the non-managerial employees in hotel service industry which is Swiss Inn Hotel. A total of 52 employees will be represented as the sample size of the study according to convenience sampling technique. The respondents will have to answer a questionnaire that consists of 5 sections that are: section A for demographic, section B for payment, section C for work, section D for advancement opportunities and section E for work performance. Through the questionnaire, the researcher will identify the facets of job satisfaction that give the most impact towards employee work performance. The research will be for one semester from December 2009 until April 2010.